Numerical calculation of the air gap flux density distribution in rotary electrical machines - Laksar, Jan; Veg, Lukas (2016 17th International Conference on Mechatronics - Mechatronika (ME), 2016)
The subject of this paper is the definition of basic parameters important to the creation of a tool or programme to numerical calculation of the real air gap flux density distribution in electrical machines. This programme will include all parameters affecting the flux density distribution like stator winding distribution, iron saturation, dimensions of the stator slots and teeth, dimensions of the rotor slots and teeth (by induction machines) and dimensions and position of permanent magnets (by PM machines). All of these parameters cannot be included in the analytical design of the electric machine and the creation and calculation of the FEM model is time-consuming. This paper includes a description of different approaches of the numerical calculations based on analytical methods. The effects on the air gap flux density distribution are calculated separately and compared with the normal component of the flux density obtained through no load FEM models. In the future, the final distribution given by the combination on mentioned effects will be calculated. The next steps to improve the programme will be calculation of the back electromotive force or the torque of the machine for which in necessary to know not only distribution of the normal component but also distribution of the tangential component of the flux density.